COST OF ILLNESS FOR CHRONIC KIDNEY DISEASE TREATMENT WITH HEMODIALYSIS IN YOGYAKARTA - Ingenida Hadning; Muhammad Heyqal Wirakarsa; Muhamad Rinaldhi Tandah Tandah (Berkala Kedokteran, 2022)
Abstract: The increase in the number of chronic kidney disease (CKD) sufferers and the expensive financing of this disease, the economic burden borne will certainly increase. This study aimed to determine the cost of illness of CKD patients undergoing hemodialysis, as well as to find out the comparison of real costs with INA-CBG’s rates. This was a pharmacoeconomic research, used the cost of illness method according to a societal perspective. The study was conducted in a type B government hospitals in Yogyakarta from January to March 2020. The population in this study were all CKD patients undergoing hemodialysis in need to mention the hospital at first. The research instruments were medical records, hospital financial data, and patient interviews. The complete data were analyzed statistically with the descriptive method and the Mann Whitney test. The number of samples was 65 patients. The results revealed the average cost of illness was 6,224,277.00 IDR for one month of treatment. The cost component that dominates was hemodialysis rate. The average real cost was 836,686 IDR for one procedure. It can be concluded that the average real cost of CKD patients with hemodialysis in the type B government hospital were significantly smaller than the INA-CBG’s rate.Keywords: Chronic Kidney Disease; Hemodialysis; Cost Of Illness; INA-CBG’s Rate